2017
DOI: 10.1186/s13075-017-1439-1
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and anti-tumor necrosis factor treatment improves endothelial function in patients with inflammatory arthritis

Abstract: BackgroundInflammatory arthritis (IA), including rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA), leads to increased cardiovascular disease occurrence probably due to atherosclerosis. One of the first stages in atherogenesis is endothelial dysfunction (ED). Therefore, we aimed to compare endothelial function (EF) in patients with IA, and to examine the effects of methotrexate (MTX) monotherapy and antitumor necrosis factor (anti-TNF) treatment with or without MTX comedicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 47 publications
3
38
0
5
Order By: Relevance
“…TNF and interleukin-6 are produced by plaque macrophages (36) and are involved in plaque evolution and destabilization (37)(38)(39)(40). Indeed, treatment with TNFi improved endothelial function in RA patients independently of inflammatory response (41). TNFi use was also associated with reduced aortic stiffness in RA independently of DAS28 change (13,42).…”
mentioning
confidence: 92%
“…TNF and interleukin-6 are produced by plaque macrophages (36) and are involved in plaque evolution and destabilization (37)(38)(39)(40). Indeed, treatment with TNFi improved endothelial function in RA patients independently of inflammatory response (41). TNFi use was also associated with reduced aortic stiffness in RA independently of DAS28 change (13,42).…”
mentioning
confidence: 92%
“…However, the doses of methotrexate administered in these studies, between 24 and 490mg/day, are considerably higher than the doses typically prescribed in patients with autoimmune disorders, between 1 and 4mg/day. In human studies, methotrexate, singly or combined with other DMARDs, has been shown to enhance endothelial function in patients with inflammatory arthritis and rheumatoid arthritis [99][100][101].…”
Section: Methotrexate Endothelial Function Arterial Stiffness and mentioning
confidence: 99%
“…Utvrđeno je da pacijenti s teškom psorijazom imaju smanjeno očekivano trajanje života te više stope kardiovaskularnog i ukupnog mortaliteta 3 20,31,35,37 . Rijetko se pojavljuju istraživanja koja navode da nema značajnog pozitivnog učinka sustavnih lijekova za psorijazu na kardiovasku-aterosklerotsku leziju 24,39 . Zaključeno je da sustavno liječenje MTX-om značajno smanjuje kardiovaskularni rizik.…”
Section: Očekivano Trajanje žIvota Kardiovaskularni Rizični čImbenicunclassified
“…Iako ovaj lijek može snižavati rizik za nastanak arterijske tromboze u pacijenata sa psorijazom, istovremeno je povezan i s hiperhomocisteinemijom koja je nepovoljni rizični čimbenik za razvoj ateroskleroze 23,37 . MTX povećava kapacitet HDL kolesterola za poticanje izbacivanja kolesterola iz pjenušavih stanica u aterosklerotskim plakovima 39 24 .…”
Section: Konvencionalno Sustavno Liječenjeunclassified